The whole spectrum of social, motor, and sensory games using every child's natural love of play to enhance key skills and promote inclusion - Sher, Barbara (Jossey-Bass, a Wiley brand, 2013)
"Fun easy games for parents and teachers to play with kids of all ages Play is increasingly recognized by neuroscientists and educators as a vital component in brain development, academic success and learning social skills. In this inspiring and useful resource, Barbara Sher provides step-by-step directions for how to use children's natural interests at different stages of their development to help them develop a wealth of sensory motor and social skills. All the games have also been designed to provide plenty of joyful opportunities for encouraging inclusion. Offers strategies for helping all kids, but especially those with special needs, to develop social, motor and sensory skills Filled with simple games using common materials that can be used by teachers, parents, and caregivers with both individual kids and groups Provides explanations and examples of how the games can aid in a child's development This resource offers parents and teachers a fun and easy way to include all children in activities that will engage all of their senses and promote important skills"--